On the move to meaningful internet systems : OTM 2018 Workshops : Confederated International Workshops: EI2N, FBM, ICSP, and Meta4eS 2018, Valletta, Malta, October 22-26, 2018, Revised selected papers /: OTM 2018 Workshops : Confederated International Workshops: EI2N, FBM, ICSP, and Meta4eS 2018, Valletta, Malta, October 22-26, 2018, Revised selected papers. (2019) - Unknown
No abstract available